Consequences for Managers of Using Single Influence Tactics and Combinations of Tactics - Falbe, Cecilia M.; Yukl, Gary (Academy of Management Journal, 1992)
The study involved analyses of incidents described from the perspective of the targets of influence attempts. We coded influence behavior in the incidents into nine tactics and classified outcomes as commitment, compliance, or resistance. Hypotheses were developed to explain the outcome of each tactic used alone and in combination. The findings supported most of the hypotheses. The most effective tactics were inspirational appeals and consultation. The least effective were pressure, legitimating, and coalition tactics. Intermediate in effectiveness were rational persuasion, ingratiation, personal appeals, and exchange tactics. ?Hard? tactics were generally less effective than ?soft? tactics. The outcomes of tactic combinations depended mostly on the potency of the component tactics.